Pengaruh Green Marketing dan Corporate Social Responsibility Terhadap Keputusan Pembelian Lampu LED Philips - Franstama Pardamean; Syafrida Hafni Sahir (Journal of Trends Economics and Accounting Research, 2023)
The aim of this study was to determine the effect of green marketing and corporate social responsibility on purchasing decisions (a case study of Philips LED lamp consumers in Medan). This type of research is associative quantitative research which aims to determine the relationship between two variables. The research population is consumers of Philips LED lights in Medan City whose number is not known with certainty. The sample size was determined using the unknown population formula and the sample results were determined to be 100 respondents. The research instrument used was a questionnaire distributed online via the Google form. The data analysis used is multiple linear regression method. Based on the results of the t test, the green marketing variable partially has a positive effect on consumer purchasing decisions for Philips LED lights in Medan City and the corporate social responsibility variable partially has a positive effect on consumer purchasing decisions for Philips LED lights in Medan City. Based on the Coefficient Test the determination of purchasing decisions can be explained by green marketing and corporate social responsibility variables.